EMANSIPASI DAN HUMANISASI PENDIDIKAN KARTINI DI ERA KECERDASAN BUATAN - Rumahorbo, Rosmawaty; Kuswandi, Dedi; Wedi, Agus (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Digital access inequality and the risk of dehumanization resulting from the integration of artificial intelligence (AI) demand a re-evaluation of the increasingly mechanistic orientation of modern education. This study aims to revitalize R.A. Kartini's educational values ??to formulate an ethical framework for inclusive and humanist education relevant to the challenges of the technological era. Through a qualitative approach with a historical-conceptual analysis design and a literature review of primary documents and recent global reports, this study examines the transformation of Kartini's thinking. Key findings indicate that Kartini's principle of freedom of thought serves as an antithesis to algorithmic bias, while her vision of humanization reinforces the urgency of authentic pedagogical relationships threatened by automation. This study also formulates the concept of "inclusive emancipation" that supports equal access for people with disabilities and identifies the alignment between Kartini's intellectual independence and the Unplugged Pedagogy strategy to maintain cognitive autonomy. It concludes that Kartini's thinking is not merely a historical legacy but has transformed into a crucial normative foundation for balancing AI innovation with human autonomy, ensuring that technology functions as an empowering tool that does not displace the essence of education as a humanizing process. ABSTRAK Ketimpangan akses digital dan risiko dehumanisasi akibat integrasi kecerdasan buatan (AI) menuntut evaluasi ulang terhadap orientasi pendidikan modern yang kian mekanistik. Studi ini bertujuan merevitalisasi nilai-nilai pendidikan R.A. Kartini untuk merumuskan kerangka etis pendidikan inklusif dan humanis yang relevan dengan tantangan era teknologi. Melalui pendekatan kualitatif dengan desain analisis historis-konseptual dan studi literatur terhadap dokumen primer serta laporan global mutakhir, penelitian ini menelaah transformasi pemikiran Kartini. Temuan utama menunjukkan bahwa prinsip pemerdekaan berpikir Kartini berfungsi sebagai antitesis terhadap bias algoritmik, sementara visi humanisasinya memperkuat urgensi relasi pedagogis autentik yang terancam oleh otomatisasi. Penelitian ini juga merumuskan konsep "emansipasi inklusif" yang mendukung kesetaraan akses bagi penyandang disabilitas serta mengidentifikasi keselarasan antara kemandirian intelektual Kartini dengan strategi Unplugged Pedagogy untuk menjaga otonomi kognitif. Disimpulkan bahwa pemikiran Kartini bukan sekadar warisan sejarah, melainkan bertransformasi menjadi landasan normatif krusial untuk menyeimbangkan inovasi AI dengan otonomi manusia, memastikan teknologi berfungsi sebagai alat pemberdayaan yang tidak menggeser esensi pendidikan sebagai proses pemanusiaan.